Testing of numerous hypotheses with the use of an optimal extended nonrandomized procedure - Koval, V. N.; Kuk, Yu. V. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
We propose a new procedure for testing hypotheses with the use of optimal statistical criteria.